Intercity Bus Terminal: Solution to Traffic Congestion in Kathmandu - Shrestha, Shreya; Phuyal, Subash (KEC Journal of Science and Engineering, 2023)
Rapid urbanization has caused highest concentration in the capital instigating traffic congestion, which is the current most serious issue in the Kathmandu valley. The need of innovative traffic management strategies in the city area and high-quality transit service has aroused the demand of an intercity bus terminal. This study examines the current and future urban scenario, addressing the future demands to provide a functional design solution. This research outlines an approach to strengthen the volume of traffic by proposing a bus terminal that limits the intercity functions outside the ring road. This ultimately contributes to the feasibility for transit-oriented development module. It focuses more on the information regarding the choice of site that has been the most determining solution to the addressed problem. The study also deals with calculations for determination of capacity of the proposed terminal. The study may create awareness among professionals about possibility of alternative solution to the congestion issue.